High Intensity Circuit Training Increases Both Aerobic Capacity in Healthy Males - Slamet Raharjo (UNIB Press, 2024)
This study aims to demonstrate the effect of high-intensity circuit training on increasing aerobic capacity in healthy men. The research employed a true-experimental design, utilizing a quantitative approach with a pretest-posttest control group structure. The participants were 20 male students aged 20-22, each with a body mass index (BMI) ranging from 19 to 23 kg/m2 and typical vital signs. The subjects were randomly assigned to G1 (control group; n=10) and G2 (high-intensity circuit training group; n=10). The high-intensity circuit training for G2 was conducted at an intensity of 85-90% of maximum heart rate (HRmax) thrice weekly for eight weeks. Aerobic capacity was assessed using the Multi-stage Fitness Test (the beep test). Data analysis was performed using paired sample t-tests and independent sample t-tests, with a significance level set at 5%. The results indicated that the average aerobic capacity in the pretest and posttest in G1 changed from 25.02±1.21 to 25.67±1.36 mL/kg/min (p=0.254), while in G2, it improved from 26.13±1.35 to 32.31±2.16 mL/kg/min (p=0.001). The findings led to the conclusion that the eight-week high-intensity circuit training intervention was effective in enhancing the aerobic capacity of healthy males.